Knee contractures as the presenting manifestation of scleroderma. Issue 6 (June 1992) - Kane-Wanger, G; Ostrov, B E; Freundlich, B
Abstract : Musculoskeletal disorders may be the primary manifestations of scleroderma. The case is reported of a patient admitted for an evaluation of severe knee flexion contractures who was diagnosed as having scleroderma but lacked the typical presenting features of the disease. Radiographic, serological, and histological support for this diagnosis are presented. Scleroderma should be considered in the diagnostic evaluation of joint contractures.